ANALISIS TINGKAT PENDAPATAN PETANI GARAM KAWASAN PESISIR DI KABUPATEN REMBANG - Aisyah Mirandi; Ida Nuraini; M.Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2019)
This study to analyzing the effect of variable land area, labor, working capital and selling prices on the income level of salt farmers in Rembang Regency. In this study using primary data through the distribution of questionnaires and direct interviews with 45 respondents of salt farmers as owners in Rembang Regency, with a list of questions prepared. The analytical method used is multiple linear regression, hypothesis testing: T statistical test, F statistical test and coefficient of determination. The results of this study indicate that the variable area of land, labor , working capital and selling prices has a significant positive effect on the income of salt farmers.